A review on environmental assessment of conversion of agriculture waste to bio-energy via different thermochemical routes: Current and future trends. (June 2021) - Alhazmi, Hatem; Loy, Adrian Chun Minh
Abstract: The investigation of the environmental impacts of different biomass valorization processes has become a "hot topic" among the academic and industrial practitioners; starting since bio-energy is opted as a clean renewable energy to mitigate the anthropogenic greenhouse gas (GHG) emissions. Life cycle assessment (LCA) is a universal friendly tool to evaluate the impact of the energy used, release of toxic substances, natural resources involved in all life cycle stages of a product or process. Herein, in this review, we are focussing on the environmental impacts of different biomass valorization-based thermochemical conversion technologies (e.g. torrefaction, pyrolysis, gasification and liquefaction). Apart from environmental impacts, the physiochemical characteristic of different agriculture waste from various regions is also being reported to provide a full overview of thermochemical conversion of agriculture waste to bio-energy. Lastly, the research gaps and future outlook in biomass thermochemical conversion are also being discussed to enlighten the future engineer and scientist on the key takeaways in this niche area. Graphical abstract: Unlabelled Image Highlights: Utilization agriculture waste as source of bio-energy via thermochemical conversion Environmental analysis of production of bio-energy via thermochemical conversion using an LCA framework. Opportunities and challenges of production of bio-energy from agriculture waste are discussed. Derivation of different environmental factors is included and discussed in detail.